The Role of Hydrodynamic Enhancement on Ignition of Lean Methane-Air Mixtures by Pulsed Nanosecond Discharges for Automotive Engine Applications. Issue 11 (2nd November 2017) - Pineda, Daniel I.; Wolk, Benjamin; Sennott, Tim; Chen, Jyh-Yuan; Dibble, Robert W.; Singleton, Daniel
ABSTRACT: The downsizing and boosting of automotive engines for increased fuel economy poses challenges in both obtaining stable ignition at boosted intake pressures and high dilution conditions. Pulsed nanosecond discharge ignition technologies have shown promise in more reliably igniting dilute charge mixtures in internal combustion engine experiments. However, reasons for this combustion enhancement remain unclear. In this study, we ignited lean methane-air mixtures in a constant volume chamber at 2 bar absolute pressure to evaluate pulsed discharge ignition using a novel electrode geometry. The in-chamber pressure history indicates faster flame development times than those produced by traditional inductive spark. High-speed schlieren imaging reveals a significant hydrodynamic component to the observed enhancement: a more wrinkled flame kernel structure and increased burning rates from increased flame surface area. Increasing the number of pulses increased expulsion of the flame kernel. Our results clarify the enhancement observed by other researchers in internal combustion engine experiments.